Implementasi Teori Belajar Sosial Dalam Program Mute (Muhammad Teladanku) Untuk Pendidikan Karakter Akhlak Mulia Di MTsN 1 Sumedang - Hermansyah, Hasbi; Nursobah, Asep; Erihadiana, Mohammad (Yayasan Cendekia Gagayunan Indonesia, 2024)
This research aims to examine the implementation of social learning theory in the Mute (Muhammad Teladanku) program at MTsN 1 Sumedang as an effort to form noble moral character in students. This program is designed with systematic stages, including planning, implementation and evaluation which focuses on integrating the moral values ​​of the Prophet Muhammad in learning. Through interactive media such as videos of the Prophet's stories and guidebooks, students are invited to understand, remember and apply the values ​​of honesty, patience and tolerance in everyday life. The research results show that the use of social learning theory-based learning methods that involve attention, retention, production, and motivation is effective in increasing student engagement and understanding. Additionally, this program utilizes educational technology to strengthen learning, especially in the context of distance learning. Program evaluation is carried out holistically, including cognitive, affective and psychomotor assessments, to measure the extent to which moral values ​​have been internalized by students. Integration of the moral values ​​of the Prophet Muhammad in the curriculum, both through Islamic Religious Education and thematic approaches in other subjects , supports the formation of students' characters who are intellectually intelligent and morally noble. With a contextual and project-based approach, this program succeeds in creating meaningful and applicable learning experiences for students.